RETRACTED: Shen et al. Cold-Pressed Nigella Sativa Oil Standardized to 3% Thymoquinone Potentiates Omega-3 Protection against Obesity-Induced Oxidative Stress, Inflammation, and Markers of Insulin Resistance Accompanied with Conversion of White to Beige Fat in Mice. Antioxidants 2020, 9, 489 - Hsin Hsueh Shen; Stephen J. Peterson; Lars Bellner; Abu Choudhary; Lior Levy; Leah Gancz; Ariel Sasson; Joseph Trainer; Rita Rezzani; Abraham Resnick; David E. Stec; Nader G. Abraham (Antioxidants, 2025)
The journal retracts the article “Cold-Pressed Nigella Sativa Oil Standardized to 3% Thymoquinone Potentiates Omega-3 Protection against Obesity-Induced Oxidative Stress, Inflammation, and Markers of Insulin Resistance Accompanied with Conversion of White to Beige Fat in Mice” [...]